2012
DOI: 10.1039/c2jm34720b
|View full text |Cite
|
Sign up to set email alerts
|

ZnSe nanoribbon/Si nanowire p–n heterojunction arrays and their photovoltaic application with graphene transparent electrodes

Abstract: The narrow indirect bandgap of Si hinders the full absorption and utilization of the solar light. Energy band engineering to the Si based photovoltaic devices is essential to address this problem. Here we report the fabrication of ZnSe nanoribbon (ZnSeNR)/Si nanowire (SiNW) p-n heterojunction arrays by directly growing or simply drop-casting the p-type ZnSeNRs on highly aligned n-type SiNW arrays. Phosphorus (P) was used as dopant to achieve robust p-type doping in the ZnSe nanostructures with a hole concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 35 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…Figure 7 summarizes the results obtained on bare and BaTiO 3 protected electrodes. Bare Cu/Cu 2 O/CuO, although exhibiting a large photocurrent in the first minutes as reported before, 34,35 unsurprisingly exhibited more than 50% decrease in current within 20 min. Under the same conditions, the protected Cu/Cu 2 O/CuO/BaTiO 3 electrodes show higher photocurrent and a decrease of 15 % in photocurrent was observed within the first 3 min.…”
Section: Stability Measurementssupporting
confidence: 69%
“…Figure 7 summarizes the results obtained on bare and BaTiO 3 protected electrodes. Bare Cu/Cu 2 O/CuO, although exhibiting a large photocurrent in the first minutes as reported before, 34,35 unsurprisingly exhibited more than 50% decrease in current within 20 min. Under the same conditions, the protected Cu/Cu 2 O/CuO/BaTiO 3 electrodes show higher photocurrent and a decrease of 15 % in photocurrent was observed within the first 3 min.…”
Section: Stability Measurementssupporting
confidence: 69%
“…The nearly linear I -V curve of the Ag/MoS 2 /Ag stacking structure in Figure S1 in Supporting Information proves that such a rectifying characteristic stems from the heterojunction between MoS 2 and Si, but not from the Ag/MoS 2 contact. The turn-on voltage is determined by extrapolating the I -V curve to the intersection of the abscissa, giving rise to a small value of ≈0.25 V. In addition, the ideality factor ( n ) of the heterojunction could be deduced to be 1.83 from the slop of the semi-log I -V curve in the forward bias direction, as shown in Figure S2 in Supporting Information, according to the following equation: [ 56 ] …”
Section: Resultsmentioning
confidence: 99%
“…1-D axial heterojunctions, based on II-VI compound semiconductor nanostructures, have also caught the eye of investigators and present excellent performance. For instance, Zhang et al constructed a kind of p-n heterojunction arrays by directly growing the p-type ZnSe nanoribbons on highly-aligned n-type Si nanowires arrays [38]. Cross-section SEM images showed that quasi-aligned ZnSe nanoribbons array was directly grown on the top of SiNWs array.…”
Section: -D Axial Heterojunctionsmentioning
confidence: 99%